Rajella paucispinosa n. sp., a new deep-water skate (Elasmobranchii, Rajidae) from the western Indian Ocean off South Mozambique, and a revised generic diagnosis - Weigmann, Simon; Stehmann, Matthias F.w.; Thiel, Ralf (Zootaxa, 2014)
A new species of the widely in temperate and tropical latitudes distributed skate genus Rajella is described based on an almost adult male specimen from the western Indian Ocean off South Mozambique. The holotype of R. paucispinosa n. sp. was caught during cruise 17 of RV ‘Vityaz’ along the deep western Indian Ocean in 1988/89. It is the northernmost record of a Rajella specimen in the western Indian Ocean. The new species is the 18th valid species of the genus and the fifth species in the western Indian Ocean. It differs from its congeners in the small maximal total length of about 50 cm and only few thorns on the dorsal surface. The new species has only two thorns on each orbit, one nuchal thorn, one right scapular thorn (left one not detectable, abraded), and one median row of tail thorns. Other species of Rajella typically have half rings of thorns on orbital rims, a triangle of thorns on nape-shoulder region, and at least three rows of tail thorns. Another conspicuous feature of the new species is the almost completely white dorsal and ventral coloration.